2019
DOI: 10.1002/ejic.201801367
|View full text |Cite
|
Sign up to set email alerts
|

Highly Luminescent Mono‐ and Dinuclear Cationic Iridium(III) Complexes Containing Phenanthroline‐Based Ancillary Ligand

Abstract: A new family of mononuclear (1-2) and dinuclear (3-5) cationic iridium(III) complexes have been synthesized and fully characterized. These complexes contain 2-(4-(trifluoromethyl)phenyl)pyridine (cf 3 ppy, L1) and 1-(4-(trifluoromethyl)phenyl)isoquinoline (cf 3 piq, L2) as cyclometalating ligands, 1,10-phenanthroline (LX-1) as the ancillary ligand and 1,4-bis(1-phenyl-1H-imidazo[4,5-f ][1,10]phenanthrolin-2-yl)benzene (biphen, LX-2) as the bridging ligand. The crystal structure of LX-2 has been determined by X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Under 320 nm, the absorption bands of complexes Ir1 – Ir3 with a high molar extinction coefficient in the level of 10 4 L·mol −1 ·cm −1 can be attributed to the spin-allowed singlet ligand-centered ( 1 LC) electronic transitions. The weaker bands in the 320–550 nm ranges are designated for metal-to-ligand (MLCT) and ligand-to-ligand (LLCT) charge transfer [ 24 ]. In 320–550 nm, the lowest energy absorption maxima of Ir2 and Ir3 are blue shifted in comparison with that of complex Ir1 .…”
Section: Resultsmentioning
confidence: 99%
“…Under 320 nm, the absorption bands of complexes Ir1 – Ir3 with a high molar extinction coefficient in the level of 10 4 L·mol −1 ·cm −1 can be attributed to the spin-allowed singlet ligand-centered ( 1 LC) electronic transitions. The weaker bands in the 320–550 nm ranges are designated for metal-to-ligand (MLCT) and ligand-to-ligand (LLCT) charge transfer [ 24 ]. In 320–550 nm, the lowest energy absorption maxima of Ir2 and Ir3 are blue shifted in comparison with that of complex Ir1 .…”
Section: Resultsmentioning
confidence: 99%
“…Among them, the development of iridium complexes with various luminescence color including blue, green, yellow, orange, and red light is a most important research direction. In particular, the design of red phosphorescent emitter is more challenging because the luminescence quantum yields decrease as emission wavelength shift to red region on account of the energy gap law [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…[12,13] Diiridium complexes are often obtained as a mixture of diastereomers, which are generally not separated. Representative recent examples of organic bridging ligands in diiridium complexes include derivatives of 4,6-diarylpyrimidine, [14] 2-phenylpyrimidine, [15,16] diarylhydrazide, [17,18] pyrazolate, [19,20] bis(phenanthroline) [21] Schiff bases, [22][23][24] pyridazine, [25] butadiene [26] and alkynes. [27] Sünkel et al first reported a diiridium complex bridged by a μ 2 -oxamidato-N,N',O,O' ligand, [28] namely complex 1 and we characterized its analogs 2 a, [29] 2 b [29] and 2 c [30] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%